Produção de monoéster via etanólise por hidrotalcitas termoativadas: síntese e caracterização - Mazzone, Lana Christiane de Albuquerque (Universidade Federal de São Carlos, 2011)
Among biofuels of the 1st generation, biodiesel stands out for its equivalent features to those of mineral diesel, however less polluting. It can be obtained by transesterification of triglyceride fats or vegetable oils by (m)ethanolysis. Aiming at improving the chemical process, different types of catalysis have been studied: i) homogeneous (acid e.g. H2SO4 and basic e.g. KOH), ii) heterogeneous (acid e.g. Montmorillonite, basic e.g. Hydrotalcite and enzymatic e.g. immobilized Lipases). However, the basic solid catalysts show themselves attractive because they are easily separated from the reaction media by filtration, avoiding both the formation of by-products and the need for biodiesel neutralization. In this group of catalysts there are some that stand out from the others, such as hydrotalcites, which, when thermically treated, result in mixed oxides with high superficial area and basicity. In this study, the efficiency of these heterogeneous catalysts containing K-Mg-Al was investigated in the transesterification of the molecule-model (CH3COOCH3) via ethanolysis in mild reaction conditions: 323K, 30 min, EtOH:AcMe=6:1 and 4 wt % of catalyst. Two methods to synthesize the hydrotalcite were used: sol-gel and impregnation. In the sol-gel, the variables fixed were: mass of carbonate (2 wt %), synthesis time (18hrs) and temperature (363K). The ratio of Mg:Al and the aging time varied in the range of 2:1-3:1 and 1-3 days, respectively. For the evaluation of this method, the incipient-wetness impregnation was used through addition of different percentage of potassium cations (2, 5 and 10%) in mixed oxide originated from the free sol-gel alkali metals hydrotalcite. Through the results of X-ray diffraction and thermal analysis it was found that the compounds produced were different in crystallinity, structural order and quantity of water molecules present in the structure. The pores of the obtained materials presented, on average, large diameters, between 14-21 nm to sol-gel samples, and 12 nm for the impregnated ones. The basicity of these were determinate by test of CO2 desorption at a programmed temperature. Among the studied parameters in the reaction of transesterification, the temperature showed the biggest influence. Thus, the most active catalysts for this condition (343K, 30 min and ratio of 6:1) were tested in regards to their reuse. The most stable catalyst in catalytic activity was the oxide (2KHTTa3-1) synthesized through precursor via sol-gel with highest quantity of magnesium in its composition and aged for one day.
Keywords: Catalisadores; Transesterificação; Óxidos mistos; Sol-gel; Transesterification; Mixed oxide; Sol-gel; ENGENHARIAS::ENGENHARIA QUIMICA